PENDIDIKAN MULTIKULTURAL DARI PERSPEKTIF H.M. RASJIDI - Dianna, Danu Nur (Universitas Muhammadiyah Surakarta, 2020)
This paper aims to study the concept of religious thought and tolerance according to Prof. H.M. Rasjidi which will be a fundamental discussion in the concept of multicultural education. The methodology in this research is a literature study of books by Prof. H.M. Rasjidi who has a discussion about the concepts of religion and tolerance. The primary source book in this study is